Analyzing the molecular mechanism of lipoprotein localization in Brucella - Goolab, Shivani; Roth, Robyn L.; van Heerden, Henriette; Crampton, Michael C. (Frontiers in Microbiology, 2015)
Bacterial lipoproteins possess comprehensive structure and functionality, ranging from bacterial physiology to pathogenic processes. As such many lipoproteins, originating from Brucella are exploited as potential vaccines to countermeasure brucellosis infection in the host. These membrane proteins are translocated from the cytoplasm to the cell membrane where they are anchored peripherally by a multifaceted targeting mechanism. Due to the variation in biological structure and activity of lipoproteins combined with the complexity of the translocation machinery, details on the mechanism of lipoprotein transport in Brucella and other pathogens are limited. The biosynthetic pathway of Brucella lipoproteins involves a distinct secretion system aiding translocation from the cytoplasm, where they are modified by lipidation, sorted by the lipoprotein localization machinery pathway and thereafter equipped for export to the outer membrane. Surface localized lipoproteins in Brucella may employ a lipoprotein flippase or the β- barrel assembly complex for translocation. This review provides an overview of the characterized Brucella outer membrane proteins that form part of the outer membrane including a handful of other characterized bacterial lipoproteins, and their mechanisms of translocation. The knowledge gained will be used to infer insight on the translocation of Brucella lipoproteins, which are categorized as vaccine candidates for treatment against brucellosis.